THE EFFECT OF AMOXICILLINE AND AMOXICILLINE + OMEPRAZOL ON ULCER HEALING AND ERADICATION OF H-PYLORI - Ali Reşit BEYLER; Ali GÖREN; Ali ÖZDEN; Kazım SOYLU; Ş. Erol KESİM and Murat PALABIYIKOĞLU and Hülya ÇETİNKAYA and Hakan BOZKAYA and Özden UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2020)
-